Risk factors, management, and future fertility of empty follicle syndrome: a retrospective study with real-world data - Luo, Zhuoye; Xu, Suxin; Hao, Guimin (Frontiers in Endocrinology, 2024)
Background: Empty follicle syndrome (EFS) is a challenging clinical problem. This study aims to identify risk factors of EFS, to present pregnancy outcomes in both EFS cycle as well as subsequent cycles, and to summarize an effective rescue protocol to improve outcomes.A retrospective analysis between 2016-2020 was conducted at our center. Stricter criteria were applied to diagnose EFS. Logistic regression analysis was used to identify risk factors for EFS. Further analyses were performed within the EFS cycle to present pregnancy outcomes and to find optimal rescue protocols. Long-term follow-up was conducted until live birth was achieved, covering at least two complete oocyte retrieval cycles.Results: Among 14,066 patients, 54 (0.38%) were identified as EFS. Patients with polycystic ovary syndrome (PCOS) had a significantly higher risk of developing EFS than non-PCOS ones (aOR = 2.67; 95% CI, 1.47 to 4.83). Within EFS patients, delaying the second oocyte retrieval by 3-6 hours significantly improved the rates of obtaining oocyte (97.4% versus 58.3%, P = 0.002), getting embryo available for transfer (92.3% versus 33.3%, P ＜ 0.001) and pregnancy (48.7% versus 8.3%, P = 0.017) compared to other delayed retrieval times. Overall, 31.5% (17/54) and 46.7% (7/15) EFS patients achieved live birth in the EFS cycle and the future cycle, respectively.PCOS is an independent risk factor for EFS, indicating that longer exposure time to human chorionic gonadotropin (hCG) may be necessary. Delaying the second oocyte retrieval by 3- hours is an effective rescue protocol for EFS patients to achieve optimal outcomes. EFS in a single cycle does not necessarily indicate future fertility decline, but repeated EFS may result in poor outcomes.